Uji Ketahanan Beton dengan Serat Limbah Bubut Besi sebagai Pavement material. - Dwicahyani, Arum; Ghufron, Ahmad; Meylida, Dhonna (MoDuluS Media Komunikasi Dunia Ilmu Sipil, 2025)
Industrial waste is a resource for green concrete. One example is iron lathe waste, which is considered hazardous and toxic (B3). This form is spiral flakes. This has potential to pollute the environment, so it needs to be recycled by used as fiber in pavement concrete. This application was chosen because paving blok does not require high-quality concrete. The quality for types C and D is K175-K125 and can be made with manual mixing. It applied as pedestrian. Fiber concrete have better durability than normal concrete in withstanding impack loads. So it is expected to less cracking. Therefore, an impact drop weight experiment was conducted. The specimen was a cylinder. The diameter was 15 cm and the height was 6 cm. The fiber variety was 0%, 6%,9% dan 12% of the concrete mix design. Impact drop weight test will provide information abaout impacts resistance and absorbed energy. The results showed that concrete containing 12% iron lathe waste fiber had 239,05% better energy absorption performance than normal concrete.